2022
DOI: 10.1085/jgp.202213081
|View full text |Cite
|
Sign up to set email alerts
|

Postdevelopmental knockout of Orai1 improves muscle pathology in a mouse model of Duchenne muscular dystrophy

Abstract: Duchenne muscular dystrophy (DMD), an X-linked disorder caused by loss-of-function mutations in the dystrophin gene, is characterized by progressive muscle degeneration and weakness. Enhanced store-operated Ca2+ entry (SOCE), a Ca2+ influx mechanism coordinated by STIM1 sensors of luminal Ca2+ within the sarcoplasmic reticulum (SR) and Ca2+-permeable Orai1 channels in the sarcolemma, is proposed to contribute to Ca2+-mediated muscle damage in DMD. To directly determine the impact of Orai1-dependent SOCE on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 105 publications
1
15
0
Order By: Relevance
“…Thus, a three- to fourfold increase in Orai1 expression could result in an increase in SOCE function even in the absence of a detectable change in STIM1 expression. Consistent with this, using a murine model of Duchenne muscular dystrophy in which SOCE activity is increased, several studies showed that this increase in SOCE correlates with a significant increment of Orai1 expression in the absence of a change in STIM1 expression ( Edwards et al, 2010 ; Zhao et al, 2012 ; Goonasekera et al, 2014 ; García-Castañeda et al, 2022 ). However, other studies have reported a significant increase in STIM1S expression in muscles from mdx mice ( Edwards et al, 2010 ; Cully et al, 2012 ).…”
Section: Discussionsupporting
confidence: 57%
“…Thus, a three- to fourfold increase in Orai1 expression could result in an increase in SOCE function even in the absence of a detectable change in STIM1 expression. Consistent with this, using a murine model of Duchenne muscular dystrophy in which SOCE activity is increased, several studies showed that this increase in SOCE correlates with a significant increment of Orai1 expression in the absence of a change in STIM1 expression ( Edwards et al, 2010 ; Zhao et al, 2012 ; Goonasekera et al, 2014 ; García-Castañeda et al, 2022 ). However, other studies have reported a significant increase in STIM1S expression in muscles from mdx mice ( Edwards et al, 2010 ; Cully et al, 2012 ).…”
Section: Discussionsupporting
confidence: 57%
“…Resting cytosolic Ca 2+ levels were significantly higher in FDB fibers isolated from 6 month old C3KO mice (Fig. 1A), suggesting intracellular Ca 2+ overload as a mechanism contributing to the dystrophic pathology in LGMD2A, as it was shown with other types of muscular dystrophies (25)(26)(27). This difference was age-dependent, as there were no differences in resting cytosolic Ca 2+ levels at 8 weeks of age (Indo-1 Ratio405/485: C3KO 0.4±0.01; WT 0.4±0.01; mean ± SEM for N=4-6 mice; P=0.94, unpaired t test), paralleling the late-onset and progressive nature of…”
Section: Loss Of Calpain 3 Perturbs Calcium Handling Through Chronic ...mentioning
confidence: 60%
“…In addition, breeding transgenic mice expressing the dominant-negative mutant Orai1 (dnOrai1) with mdx mice resulted in a significant improvement in mouse skeletal muscle histopathology, further supporting the involvement of STIM1-Orai1 in the progression of DMD [74]. A recent study also showed that crossing mdx mice with muscle-specific Orai1 knockout mdx mice (mdx-Orai1 KO mice) also resulted in normalizing Ca 2+ homeostasis and promoting sarcolemmal integrity/stability [76].…”
Section: Dysregulation Of Sarcolemmal Calcium Channels In Dmdmentioning
confidence: 85%